Genetic resources of African mahogany in Brazil: genomic diversity and structure of forest plantations - Júlio Cézar Tannure Faria; Enéas Ricardo Konzen; Marcos Vinicius Winckler Caldeira; Tiago de Oliveira Godinho; Luciana Prata Maluf; Sarah Ola Moreira; Carolina da Silva Carvalho; Bárbara Simões Santos Leal; Cássia dos Santos Azevedo; Dione Richer Momolli; Gracielle Teodora da Costa Pinto Coelho; Conceição de Maria Batista de Oliveira; et al. (BMC Plant Biology, 2024)
Abstract Background African mahogany species (Khaya sp.) have been introduced to Brazil gaining increasing economic interest over the last years, as they produce high quality wood for industrial applications. To this date, however, the knowledge available on the genetic basis of African mahogany plantations in Brazil is limited, which has driven this study to examine the extent of genetic diversity and structure of three cultivated species (Khaya grandifoliola, Khaya senegalensis and Khaya ivorensis) and their prospects for forest breeding. Results In total, 115 individuals were genotyped (48 of K. grandifoliola, 34 of K. senegalensis and 33 of K. ivorensis) for 3,330 filtered neutral loci obtained from genotyping-by-sequencing for the three species. The number of SNPs varied from 2,951 in K. ivorensis to 4,754 in K. senegalensis. Multiloci clustering, principal component analysis, Bayesian structure and network analyses showed a clear genetic separation among the three species. Structure analysis also showed internal structure within each species, highlighting genetic subgroups that could be sampled for selecting distinct genotypes for further breeding, although the genetic distances are moderate to low. Conclusion In our study, SNP markers efficiently assessed the genomic diversity of African mahogany forest plantations in Brazil. Our genetic data clearly separated the three Khaya species. Moreover, pairwise estimates of genetic distances among individuals within each species showed considerable genetic divergence among individuals. By genotyping 115 pre-selected individuals with desirable growth traits, allowed us not only to recommend superior genotypes but also to identify genetically distinct individuals for use in breeding crosses.